In-plane dielectric constant and conductivity of confined water - R. Wang; M. Souilamas; A. Esfandiar; R. Fabregas; S. Benaglia; H. Nevison-Andrews; Q. Yang; J. Normansell; P. Ares; G. Ferrari; A. Principi; A. K. Geim; et al. (Nature, 2025)
Abstract Water is essential for almost every aspect of life on our planet and, unsurprisingly, its properties have been studied in great detail1. However, disproportionately little remains known about the electrical properties of interfacial and strongly confined water2,3, in which the structure deviates from that of bulk water, becoming distinctly layered4,5. The structural change is expected to affect the conductivity of water and particularly its polarizability, which in turn modifies intermolecular forces that play a crucial role in many physical and chemical processes6–9. Here we use scanning dielectric microscopy (SDM)10 to probe the in-plane electrical properties of water confined between atomically flat surfaces separated by distances down to 1 nm. For confinement exceeding several nanometres, water exhibits an in-plane dielectric constant close to that of bulk water and its proton conductivity is notably enhanced, gradually increasing with decreasing water thickness. This trend abruptly changes when the confined water becomes only a few molecules thick. Its in-plane dielectric constant reaches large, ferroelectric-like values of about 1,000, whereas the conductivity peaks at several S m−1, close to values characteristic of superionic liquids. We attribute the enhancement to strongly disordered hydrogen bonding induced by the few-layer confinement, which facilitates both easier in-plane polarization of molecular dipoles and faster proton exchange. This insight into the electrical properties of nanoconfined water is important for understanding many phenomena that occur at aqueous interfaces and in nanoscale pores.